Ganancias ilícitas de la delincuencia transnacional e instrumentos penales para disuadirla - Moya Guillem, Clara (Estudios penales y criminologicos, 2021)
Profit is the main motivation for transnational crime. Consequently, if fight is to be sought, such an incentive should be pursued. For this, three legal principles of the General Part of Spanish Criminal Law that affect the profits derived from crime are useful: civil liability, the confiscation of profits and the penalty of a proportional fine. But, surprisingly, they are not usually used in relation to transnational crimes regulated in the Spanish Criminal Code. The aim of this paper is precisely to examine the legal-criminal consequences currently provided for in transnational crimes (in particular, those that suppress drug, arms and human trafficking), as well as their application in the most recent jurisprudence. In this way, it will be possible to determine if they are effective in terms of general prevention or if the use of other instruments would be more effective.